The Persistence of Buildings and the Context Problem - Fabio Bacchini (Footprint)
Raising the persistence question about architectural entities consists in asking what is necessary and sufficient for a past or future architectural entity, like a building, to exist now. In this paper I investigate how the persistence question about buildings is affected by their spatial relocation. Why do we normally doubt that Notre Dame can survive its meticulous stone-by-stone transfer to Las Vegas? I argue that, since architectural plans are not capable of specifying all the constitutive properties of a building, the source of differentiation among constitutive and non-constitutive properties for buildings lies in a property’s being eligible or not eligible to be aesthetically relevant in the aesthetic judgements about them. As a matter of fact, our aesthetic judgements about buildings often concern, and are grounded on, extrinsic contextual properties. This explains why buildings can usually not survive relocation: because normally there is no basis for ruling out any extrinsic contextual feature of the building as inessential. I also try to explain why the change from thirteenth century Paris to contemporary Paris proved not to be lethal to Notre Dame’s persistence, in spite of its being more significant than other imaginary context changes that we would easily count as fatal.